Есть тождество, есть решение(вложения). Прошу объяснить по шагам и с формулами все действия.

2

Ответы и объяснения

Лучший Ответ!
2013-01-26T00:29:49+04:00

используем формулу

 

                tga+tgb

tg(a+b)=---------------

              1-tga*tgb

имеем

tga+tgb                          tga+tgb

------------- - (tga+tgb)-  -------------*tga*tgb=

1-tga*tgb                       1-tga*tgb

 

tga+tgb-(tga+tgb)(1-tga*tgb)-(tga+tgb)*tga*tgb

------------------------------------------------------------ =

                         1-tga*tgb

 

tga+tgb-(tga+tgb)+(tga+tgb)*tga*tgb-(tga+tgb)*tga*tgb

---------------------------------------------------------------------- = 0

                          1-tga*tgb

2013-01-26T01:38:49+04:00

по формуле:tg(a+b)=(tga+tgb)/(1-tga*tgb)              

 

(tga+tgb)/(1-tga*tgb)-(tga+tgb)-(tga+епи)/(1-tga*tgb) * tga*tgb=0

(tga+tgb-(tga+tgb)(1-tga*tgb)-(tga+tgb)*tga*tgb)/(1-tga*tgb)=0

(tga+tgb-(tga+tgb)+(tga+tgb)*tga*tgb-(tga+tgb)*tga*tgb)/(1-tga*tgb)=0